PEMBELAJARAN BERBASIS MOBILE (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2014)
One of the advances or progress in the field of education is shown by the process of learning that no longer teacher-centered but student-centered. The issue requires the experts to develop learning process which implicates to students centered (student centered learning). One model that leads to student centered learning is mobile learning (m-Learning). The purpose of this paper was to (a) identify and gain an overview of the mobile-based learning, and (b) to determine and obtain an overview of the mobile-based learning process. This model of learning combines elements such as technology device, social aspect, and the students themselves. The process of learning was begun by downloading the learning material application to be installed into the hand phone or mobile device. After finishing the installation process, the users then can start to browse for the material. The facilities provided by the material supplier are different, depends on the needs and the purpose to be achieved. Kemajuan dalam bidang pendidikan salah satunya ditandai dengan proses pembelajaran yang tidak lagi berpusat pada guru. Permasalahan tersebut menuntut para ahli untuk mengembangkan pembelajaran yang berimplikasi pada pembelajaran yang berpusat pada peserta didik (student centered learning). Salah satu model yang mengarah pada student centered learning adalah mobile learning (m-Learning). Adapun tujuan dalam penulisan artikel ini adalah (a) untuk mengetahui dan memperoleh gambaran tentang pembelajaran berbasis mobile, dan (b) untuk mengetahui dan memperoleh gambaran mengenai proses pembelajaran berbasis mobile. Pembelajaran ini menggabungkan beberapa aspek diantaranya perangkat teknologi, aspek sosial, dan peserta didik. Pembelajaran dimulai dengan mengunduh aplikasi materi pelajaran untuk diinstall di telepon seluler (handphone). Setelah instalasi selesai, pengguna dapat memulai menjelajah materi tersebut. Fasilitas yang disediakan masing-masing penyedia aplikasi materi berbeda-beda, tergantung kebutuhan dan tujuan yang ingin dicapai.
Keywords: mobile learning; teknologi; peserta didik; technology; students